Group Presentation as One Way of Increasing Students’ Participation in the Classroom - Karjo, Clara Herlina (Lingua Cultura, 2008)
Teaching English (TOEFL) to a class of 50 students or more is a difficult task for a lecturer. Some problems will occur, for example, the improbability for all students to get equal teacher’s attention and equal chance for learning and studying in class. To overcome these problems, the writer conducts a quasi-experimental research involving 100 students in her two classes in Bina Nusantara University. In this research, the writer applies the group presentation method for teaching TOEFL for one semester. The research shows that group scores are slightly higher than individual students’ scores.Keywords: